Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1519/jsc.0b013e3181a00c80
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-Hydroxy-β-Methylbutyrate Supplementation During Resistance Training on Strength, Body Composition, and Muscle Damage in Trained and Untrained Young Men: A Meta-Analysis

Abstract: Beta-hydroxy-beta-methylbutyrate (HMB) is a popular supplement in the resistance training community, with its use supported by claims of increased strength, muscle growth, and improved recovery; however, research outcomes are variable. Therefore, we meta-analyzed the effectiveness of HMB on strength, body composition, and muscle damage. Nine qualifying studies yielded 14 comparisons subcategorized by training experience (trained, untrained) to provide 12-13 estimates of strength (upper body, lower body, overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 25 publications
2
50
0
Order By: Relevance
“…It has been suggested that the HMB effect on body composition is inconsequential 23 .Some studies reported that HMB was unable to change the body composition of athletes involved in resistance training (22), water polo, rowing 9 or football 17,24 .On the other hand, a number of studies failed to confirm these results and indicated that HMB supplementation during 2-to 12-weeks of training promoted significantly greater changes in FFM and fat loss in trained and untrained men and women 4,5,25,26 . Based on previous studies, the data about the effect of HMB supplementation on body composition is inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the HMB effect on body composition is inconsequential 23 .Some studies reported that HMB was unable to change the body composition of athletes involved in resistance training (22), water polo, rowing 9 or football 17,24 .On the other hand, a number of studies failed to confirm these results and indicated that HMB supplementation during 2-to 12-weeks of training promoted significantly greater changes in FFM and fat loss in trained and untrained men and women 4,5,25,26 . Based on previous studies, the data about the effect of HMB supplementation on body composition is inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…β-Hydroxy-β-methylbutyrate (HMB) is a metabolite of the amino acid leucine that has previously been shown to increase protein synthesis, strength and power, and decrease circulating markers of muscle damage [19]. To date, three studies only have been evaluated the effect of HMB on immune function during RE in humans [6,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…This meta-analysis included only seven RCTs on HMB (and 9 intervention arms), all of which were included in the meta-analysis by Rowlands and Thomson (2009). The Panel considers that this meta-analysis does not provide evidence for the scientific substantiation of the claims in addition to that of the meta-analysis by Rowlands and Thomson (2009).…”
Section: Scientific Substantiation Of the Claimed Effectmentioning
confidence: 99%
“…In the meta-analysis by Rowlands and Thomson (2009), a total of five studies, including eight effect estimates, addressed the effects of HMB supplementation on muscle damage during resistance training by means of blood concentrations of CK as a marker of muscle membrane damage (Jówko et al, 2001;Kreider et al, 1999;Kreider et al, 2000;Nissen et al, 1996;Panton et al, 2000). All intervention arms used doses of HMB of 3.0 g/day except one (i.e.…”
Section: Reduction Of Muscle Tissue Damage During Exercise (Id 1577 mentioning
confidence: 99%
See 1 more Smart Citation